A simple and accurate evaluation of hydrogen-ion concentrations in aqueous solutions of fixed ionic strength - Molina, M. [UNESP]; Melios, C. [UNESP]; Tognolli, J. O. [UNESP]; Luchiari, L. C. [UNESP]; Jafelicci, M. [UNESP] (Elsevier, 1979)
A method for determining hydrogen-ion concentrations based on emf measurements of cells consisting of glass electrodes coupled with modified calomel reference electrodes is described. The calibration is effected against dilute perchloric acid and sodium hydroxide solutions; a correction for liquid junction potentials is applied. The accuracy and precision of different methods used for calibrating glass electrodes in cells with liquid junctions is discussed and the effect of different calibrations on the determination of equilibrium constants (namely, protonation constants of glycine and stability constants of copper(II)-glycine complexes) is demonstrated. The constants determined are compared with those already published for the same systems. © 1979 Elsevier Sequoia S.A.